Application Of Fuzzy Logic In Umkm Recommendations Upgrade Using The Sugeno Method At The Cooperative Office Of The City Of Bengkulu - Ristika Ristika; Dewi Suranti; Eko Suryana (Jurnal Komputer, Informasi dan Teknologi, 2023)
The application of fuzzy logic in the recommendation of MSMEs to upgrade at the Bengkulu City Cooperative Office can help provide assessment results for MSMEs based on assessment criteria so that MSMEs are obtained that are upgraded feasible or not feasible. The Sugeno method will analyze MSME assessment data by looking at the number of workers, capital, and turnover of each MSME which will then calculate the z value in each rule where there are 54 rule compositions used so that the final value for each MSME can be known. Based on the blackbox testing that has been carried out, it is found that the functionality of the MSME recommendation application for upgrading at the Bengkul City Cooperative Service runs well as expected and is able to analyze MSME assessment data through the Sugeno Fuzzy Method to determine recommendations for MSME eligibility for upgrading..